The Neolithic - Lena Holm (Current Swedish Archaeology, 1995)
Publications from the time period 1986-1990 concerning the Neolithic are characterized by variation. This is seen in the different approaches and regional differences based on various archaeological conditions. Studies of settlements and economic/social aspects of the societies are in majority together with an emphasis on neolithisation processes. Some studies concern theoretical approaches and methods and applications. South Sweden, with Scania in focus, is the most well-documented region, with regional variations in the archaeological record interpreted as cultural and social differences. In central Sweden comparatively few contributions discuss problems of settlements and social and cultural structures. In Norrland, finally, differences in the archaeological record between and within coastal and inland regions are evident, signifying various Neolithic groups.